PENGARUH INTENSITAS PENGGUNAAN SMARTPHONE DAN SUMBER BELAJAR TERHADAP KEMAMPUAN KOGNITIF SISWA SMKS KRISTEN 2 TOMOHON - Fanly Kuhu; Joseph Kambey; Iwan Kandori; Starry Wokas (Literacy: Jurnal Pendidikan Ekonomi, 2024)
This research aims to determine the partial and simultaneous influence of the intensity of smartphone use and learning resources on the cognitive abilities of FASE E Class X< span> and XI < span>i< span>n< span> SMKS Kristen 2 Tomohon students < span>This research method uses quantitative methods with multiple regression analysis with a total of 51 respondents class X < span>and XI < span>FASE E students The research results show that the t value for the intensity of Smartphone use is greater than the t table < span>3 675 gt; 1 677< span> while the t value for Learning Resources is also greater than the t table < span>2 034 gt; 1 677< span> where it can be concluded that there is a partially significant influence on the intensity of Smartphone use and learning resources on students cognitive abilities the simultaneous influence can be seen from the calculated f value where the calculated f is greater than f table < span>8 618< span> gt; 3 19< span> meaning that there is a significant simultaneous influence on the intensity of smartphone use and learning resources on FASE students cognitive abilities E Class X < span>and XI < span>at Christian Vocational School 2 Tomohon< span> < span>< span>< p>